Effect of temperature anisotropy on the dynamics of geodesic acoustic modes. (6th February 2023) - Sama, J.N.; Biancalani, A.; Bottino, A.; Chavdarovski, I.; Del Sarto, D.; Ghizzo, A.; Hayward-Schneider, T.; Lauber, Ph.; Rettino, B.; Vannini, F.
Abstract : In this work, we revisit the linear gyro-kinetic theory of geodesic acoustic modes (GAMs) and derive a general dispersion relation for an arbitrary equilibrium distribution function of ions. A bi-Maxwellian distribution of ions is then used to study the effects of ion temperature anisotropy on GAM frequency and growth rate. We find that ion temperature anisotropy yields sensible modifications to both the GAM frequency and growth rate as both tend to increase with anisotropy and these results are strongly affected by the electron to ion temperature ratio.